Effects of concentrated feed enriched with zeolite and glycerin on productivity of beef cattle (Mongolian Journal of Agricultural Sciences, 2018)
Sixteen native breeds of cattle (n=16) were selected as experimental animal and divided into two control and two experimental group.  The cattle for this study were two months old native breeds that all castrated males with average live weight 270±5 kg. During the experimental period cattle in first control group were grazed on open pasture, while second control group were kept in door and fed by well-balanced concentrated feed for beef cattle. However first experimental group were fed by feed ration enriched with 2% of native zeolite, whereas second experimental group was provided by ration with 2% of zeolite and 6% of glycerin. All of these cattle in two different groups were fed for 52 days in total, which divided into preparation and experimental periods of 7 and 45 days. Daily body weight of cattle in first control group was declined by 15 kg (357.5g) while it was increased by 22.25 kg (530g) in second control, 30.04 kg (714.5 g) in first experimental and 24.75 kg (589.3 g) in second experimental groups (p